A computational evaluation of the passenger crash position in civil aircraft - Haidar, Raf (1995)
The crash of the Boeing 737-400 G-OBME at Kegworth on the 8th January 1989 provided an opportunity to investigate how the passengers were injured during the crash. A computer simulation was subsequently set up to assess the kinematics of the passengers and to establish the likely forces which they would have experienced during the crash.